A generalizations of the ternary Cantor set - Merino Toapanta, Andres (2020)
In this work, we show a generalization to the ternary Cantor set based on the beta-expantion of a number, futhermore, we present that, under appropriate hypotheses, this extension also corresponds to a constructive way of the definition of the ternary Cantor set . Finally, we prove that these sets that are, in effect, Cantor sets.